(untitled) (Panacea Journal of Medical Sciences, 2021)
Background: “Health insurance” is an insurance that covers the whole or part of the risk of a person incurring medical expenses, spreading the risk over a large number of persons. Objectives: To find out proportion of insurance coverage among patients admitted in a tertiary care hospital and to assess reasons for non-coverage of insurance. Materials and Methods: Hospital based cross sectional study was conducted among 272 patients admitted in a tertiary care hospital. After taking informed consent, interview of patient was conducted. Data was entered in a predesigned, semi-structured questionnaire. Detailed interview of the patient was conducted regarding coverage of insurance, type of insurance used, reasons for enrolling insurance and reasons for not enrolling insurance. Data was analysed by using EPI INFO statistical software.